DUAL KOTHE-TOEPLITZ UNTUK RUANG BARISAN VEKTOR - Ahmad, Mizan (Jurnal Matematika UNAND, 2023)
In this paper, we discuss about some classes of vector sequence spaceson w(R^n). We observe their completeness and the relationships between them. At the end of this paper, we construct the Kothe-Toeplitz dual of some vector sequence spaces.